Reasons for parents and guardians for non-adherence to Human Papilloma Virus vaccination: Scoping Review (Research, Society and Development, 2022)
The HPV vaccine was introduced in Brazil's National Immunization Program (PNI) in 2014. Despite efforts by the Ministry of Health to increase vaccine coverage, the number of vaccinated adolescents is not satisfactory. This study aimed to synthesize the scientific evidence on the reasons that lead parents and guardians to refuse to vaccinate children and adolescents against HPV. The methodology used was through a Scope Review. For the construction of the methodological steps, the criteria of the Joanna Briggs Institute and the PRISMA-SCR were respected. The research was carried out in six electronic databases, on the CAPES Journal Portal. The extracted data were analyzed and synthesized in narrative form. A total of 8535 records, 23 studies were retrieved and kept for review. Of the publications, they had a quantitative (52.17%), qualitative (43.48%) and mixed (4.35%) approach. Four categories emerged from the findings: vaccine safety and fear of adverse events; early age and vaccine against sexually transmitted disease; cultural and religious influence; and ignorance and fake news. This study allowed us to investigate and deepen the knowledge about the reasons that influence parents' decision-making regarding HPV vaccination.